The backtrack - La Rosa, Erin, 1985- (Canary Street Press, 2024)
"Nearly twenty years ago, Sam Leto left her small hometown of Tybee Island, Georgia, to pursue her dreams of becoming a pilot. While she'd prefer to keep flying away from her painful childhood memories, her beloved grandmother Pearl decides it's time to sell the family home. Reluctantly, Sam is summoned back to pack up the house. The 2000s nostalgia from Sam's old bedroom hits immediately: Fall Out Boy posters, drawers of roll-on body glitter and even her favorite CD player with a mixtape from her best friend, Damon Rocha. Damon was always a safe place and Sam often wonders what if her teenage self admitted her feelings for him back then...Mysteriously, the CD player still works all these years later. And somehow it has the power to show Sam an alternate version of her life."--